How does Injury Severity Score derived from International Classification of Diseases Programs for Injury Categorization using International Classification of Diseases, Tenth Revision, Clinical Modification codes perform compared with Injury Severity Score derived from Trauma Quality Improvement Program?. Issue 1 (30th January 2023) - Wan, Vivian; Reddy, Susheel; Thomas, Arielle; Issa, Nabil; Posluszny, Joseph; Schwulst, Steven; Shapiro, Michael; Alam, Hasan; Bilimoria, Karl Y.; Stey, Anne M.
Abstract : ICDPIC calculates ISS with moderate concordance with TQIP after transition to ICD-10 codes but requires caution in certain populations. ICDPIC performs best at high ISS ranges and for firearm, motor-vehicle, and pedestrian mechanisms. #trauma #ICDPIC #injuryseverity. Abstract : BACKGROUND: Injury Severity Score (ISS) is a measurement of injury severity based on the Abbreviated Injury Scale. Because of the difficulty and expense of Abbreviated Injury Scale coding, there have been recent efforts in mapping ISS from administrative International Classification of Diseases ( ICD ) codes instead. Specifically, the open source and freely available International Classification of Diseases Programs for Injury Categorization (ICDPIC) in R (Foundation for Statistical Computing, Vienna, Austria) converts International Classification of Diseases, Ninth Revision, codes to ISS. This study aims to compare ICDPIC calculations versus manually derived Trauma Quality Improvement Program (TQIP) calculations for International Classification of Diseases, Tenth Revision ( ICD-10 ), codes. Moderate concordance was chosen as the hypothetical relationship because of previous work by both Fleischman et al. ( J Trauma Nurs. 2017;24(1):4–14) who found moderate to substantial concordance between ICDPIC and ISS and Di Bartolomeo et al. ( Scand J Trauma Resusc Emerg Med. 2010;18(1):17) who found none to slight concordance. Given these very different findings, we thought it reasonable to predict moderate concordance with the use of more detailed ICD-10 codes. METHODS: This was an observational cohort study of 1, 040, 728 encounters in the TQIP registry for the year 2018. International Classification of Diseases Programs for Injury Categorization in R was used to derive ISS from the ICD-10 codes in the registry. The resulting scores were compared with the manually derived ISS in TQIP. RESULTS: The median difference between ISS calculated by ICDPIC-2021 using ICD-10, Clinical Modification (ISS-ICDPIC), and manually derived ISS was −3 (95% confidence interval, −5 to 0), while the mean difference was −2.09 (95% confidence interval, −2.10 to −2.07). There was substantial concordance between ISS-ICDPIC and manually derived ISS ( κ = 0.66). The ISS-ICDPIC was a better predictor of mortality (area under the curve, 0.853 vs. 0.836) but a worse predictor of intensive care unit admission (area under the curve, 0.741 vs. 0.757) and hospital stay ≥10 days (AUC, 0.701 vs. 0.743). The ICDPIC has substantial concordance with TQIP for the firearm ( κ = 0.69), motor vehicle trauma ( κ = 0.71), and pedestrian ( κ = 0.73) injury mechanisms. CONCLUSION: When TQIP data are unavailable, ICDPIC remains a valid way to calculate ISS after transition to ICD-10 codes. The ISS-ICDPIC performs well in predicting a number of outcomes of interest but is best served as a predictor of mortality. LEVEL OF EVIDENCE: Prognostic and Epidemiological; Level III. Abstract :